Tightening Leakage Resilience of the Suffix Keyed Sponge - Berendsen, Henk; Mennink, Bart (IACR Transactions on Symmetric Cryptology, 2024)
Lightweight cryptographic constructions are often optimized on multiple aspects that put the security bounds to the limit. In this respect, it is important to obtain security bounds that are tight and give an accurate and exact indication of the generic security. However, whereas for black-box security bounds it has become common practice to argue tightness of security bounds, for leakage resilience security bounds this is not the case. This is unfortunate, as for leakage resilience results, tightness is even more important as there is already a lossiness incurred in capturing the actual leakage by a theoretical model in the first place.In this work, we consider the SuKS (Suffix Keyed Sponge) PRF construction and investigate tightness of the leakage resilience bound of Dobraunig and Mennink (ToSC 2019). We observe that, although their black-box security result is tight, their leakage resilience bound is not tight in their bounded leakage term λ. We observe that this is caused by the fact that parts of the security bound contain a term covering multicollisions and a term covering leakage, but an adversary is unable to combine both. We next consider improved security of the SuKS for two types of leakage: fixed position leakage, where the adversary directly learns the value of λ bits of a secret state, and Hamming weight leakage, where the Hamming weight of a fixed part of the state is leaked. For fixed position leakage, a very generous form of bounded leakage, we improve the original bound by making wise use of the multicollision limit function of Daemen et al. (ASIACRYPT 2017). For the more realistic setting of Hamming weight leakage, we structurally revisit the multicollision limit function analysis by including Hamming weight in the computation, a problem that is difficult on its own due to the non-uniform character of this type of leakage. In both cases, we improve and tighten the leakage resilience bound of Dobraunig and Mennink. The improved bound for the SuKS has immediate consequences for the leakage resilience of the NIST lightweight cryptography competition finalist ISAP v2, an authenticated encryption scheme that uses the SuKS internally.